THE FINANCIAL RESTORATION OF INSURANCE COMPANIES - LUMINITA TULEASCA (Challenges of the Knowledge Society)
The entire legal regulation of the insurance market is focused on the protection of the insurance policies holders, on keeping their trust in the insurance system and on the maintenance of the financial market steadiness. Noticing and solving the problems prior to the occurrence of insurers’ insolvency situation represents a fundamental aspect for the means of achieving such objective.By this survey we will analyse the financial restoration procedure of the insurance companies, Romanian legal entities, through the perspective of the whole aggregate of legal issues involved by this extremely complex and sensitive process required by the special nature of the insurance companies and by the impact of the activities carried out by these companies for the economic and social life of a state.Thus, there have been pointed out the particularities and the special nature of the insurance companies’ financial restoration as compared to the reorganization of the regular trade companies, the insurers’ means of avoiding the business failure, of avoiding the bankruptcy.